Gaseous and thermal analysis of winter garden used for air regeneration throughout office buildings - Rymarov, Andrey; Parfenteva, Natalia; Valančius, Kęstutis; Paulauskaitė, Sabina; Misevičiūtė, Violeta (Journal of Environmental Engineering and Landscape Management, 2018)
Ecological problems are inherent in the issue of air quality in the buildings. The main goal thus becomes the creation of indoor clime, where concentration of the detrimental impurities, such as carbon dioxide, would not exceed established norms. Thus, it is proposed to develop an alternative system of ventilation, which would ensure necessary indoor climate without outside air use. In order to decrease the levels of it inside the buildings, it is suggested to use a winter garden with much greenery, so that the air would be regenerated since the carbon dioxide would be absorbed and oxygen would be evolved. The current work reveals the study results of thermal, air and gas conditions in a winter garden upon the office building. The proposed methodology based on the ANSYS-CFX software, ensures a successful calculation of heating and aerial regimes within buildings that might differ in accordance with various engineering practices.